Impactos sociales y ambientales de la explotación de hidrocarburos en el municipio de Papantla, Veracruz (México) - Victoria Chenaut (e-cadernos ces)
This article highlights the social and environmental impacts that occur due to the process of exploration and exploitation of hydrocarbons (oil and gas) in the municipality of Papantla, Veracruz, indicating some of the changes that took place as a result of the neoliberal policies applied in the energetic sector. In the first section, I point out the effects that oil activities have on the communities and the tensions that exist between the inhabitants and the oil companies. In the second, I analyze two cases of protests by those affected that led to legal actions being taken against them. This implies a criminalization of social protest that favors extractive policies.